Valorization of Lignocellulosic Biomass to Biofuel: A Systematic Review - Mbuyu Germain Ntunka; Siphesihle Mangena Khumalo; Thobeka Pearl Makhathini; Sphesihle Mtsweni; Marc Mulamba Tshibangu; Joseph Kapuku Bwapwa (ChemEngineering, 2025)
Lignocellulosic biomass, derived from plant materials, represents a renewable alternative to fossil fuels and plays a crucial role in advancing environmental sustainability. This systematic review investigates recent developments in the conversion of lignocellulosic biomass into biofuels, with a focus on pre-treatment technologies that enhance enzymatic hydrolysis, a critical step in efficient biofuel production. This review addresses two primary questions: (1) What are the most effective pre-treatment methods for enhancing enzymatic hydrolysis in lignocellulosic biomass conversion? (2) How do these pre-treatment methods compare in terms of efficiency, environmental impact, and economic feasibility? Consequently, studies were selected based on inclusion criteria that focus on research investigating these pre-treatment methods and their comparative performance. A structured search of original studies was applied across databases such as Crossref, Google Scholar, Scopus, PubMed, and Semantic Scholar, resulting in the inclusion of 17 peer-reviewed articles published between 2019 and 2024. The findings highlight effective pre-treatment methods that significantly improve enzymatic accessibility and bioethanol yields. However, ongoing challenges such as feedstock variability, process efficiency, and cost-effectiveness remain. These results highlight the need for further research and development to optimize conversion technologies and identify new areas for exploration.